Strategi Pembelajaran Aktif Praktik Pedalangan - Hariyadi Tri Putranto (Institut Seni Indonesia Surakarta, 2008)
Review of learning strategy in Praktik Pedalangan(puppetry practice) subject matter is based on many problems. The material given is hard enough so that the students final score is not good. The strategy taken overcome the problems is by applying active learning model. Try out shows that SAP (the lecture items) and GBPP (the guidelines for teaching programs)are compsed based on the previous SAP and GBPP. Teaching material is provided in a book while teaching media is provided in CD. Lecture strategy is executed with coqnitive sharpening system, verbal instruction, demonstration, interpretation,evaluation,and creativities. There is an increase in the final score of the students after the application of active learning strategy to Praktik Pedalangan III.Keyword : model, active learning, Praktik pedalangan(pupperty practice).